Which is a factor of 6x2 + x − 7? x + 1, 2x + 1, 6x + 7 ,3x + 7

Answers

Answer 1
Answer:

Answer:

The correct answer is 6x +7

Step-by-step explanation:

It is given a polynomial  6x^2 + x − 7

Factorization of  6x^2 + x − 7

Using splitting method

6x^2 + x − 7 =  6x^2 - 6x  + 7x − 7

= 6x(x - 1) + 7 (x - 1)       (take 6x and 7 as common)

= (x - 1)(6x +7)

Therefore the factors of  6x^2 + x − 7 are (x - 1) and (6x + 7)

Therefore the correct answer is (6x + 7)

Answer 2
Answer:

Answer:

6x+7

Step-by-step explanation:

If you factor this quadratic,

your 2 factors are:

(6x+7)(x-1)


Related Questions

15 points because I need it quickly!! I will give brainliest to first answerMiss Holman gave a 90-cent tip to a waitress for serving a meal costing $6.00, before tax. a) What percent of the bill was her tip? b) If tax was 6.25%, what was the total bill including tip?
How do I solve -25 + 4(25-10)÷5
Greatest Common Factor of 55 and 77
There were 21 students in Travis's fourth-grade class at the end of the year. During the year four new students joined his class, and two moved away. One student was transferred to another fourth-grade teacher. How many students were there in the beginning of the year?
The value of y varies directly with x2, and y = 64 when x = 4.What is the value of y when x = 6?

What is the value of 7/8 +3/4

Answers

Find the common denominator:

7/8+6/8
= 13/8 or 1 (5)/(8)
Since 3/4 equals 6/8, you do 7/8 + 6/8 = 11/8 and that can be simplified to 1 and 3/8 and put into decimal form like 1.375.

26 points of the second floor of 5236 is how many more ?

Answers

the answer is (5210) more
5210 is the answer...did i get it right?

Fruit: Sugar in 2:3
If 15kg of sugar is used,how much fruit?

Answers

1 kg...............2/3 fr
15 kg..............x fr
x=15·2/3
x=5·2
x=10 fruits

Answer:10
So the 2:3 means that for every 2kg of fruit you have there are 3kg of sugar.Divide the sugar by three, giving you 5kg. Then multiply that by two to find the fruit = 10kg.10kg:15kg

1/5m + 6 = 3/4
What is m?

Answers

1/5m + 6 = 3/4

subtract 6 from each side

1/5m = 3/4 - 6

divide 1/5 from each side

m = 3/4÷1/5 - 6/5

simplify

m= 3/4 × 5 - 6/5
m = 15/4 - 6/5
m = 75/20 - 24/20
m = 51/20

m = 2 11/20


Solve the equation below

Answers

1/3(12+x) = -8 (6-x)

Distribute the 1/3 and the -8 through their parentheses

4 + 1/3x = -48 + 8x

subtract 4 from each side

1/3x = -52 + 8x

subtract 8x from each side

1/3x - 8x = -52

combine like terms

1/3x - 24/3x = -52
-23/3x = -52

divide each side by -23/3 (multiply the reciprocal of the divisor)

x = -52 × -3/23
x = 156/23

x = 6 18/23 or 6.78
(1/3)(12+x)=(-8)(6-x)
(1/3)*12 + (1/3)*x = -8*6 - (-8)*x
4 + 1/3x = -48 + 8x
1/3x - 8x = -48 - 4
-23/3x = -52
x = 156/23

Part 5: Common Core Practice What is the best name that describes all the figures below? Lesson 32

Answers

Parallelogram because all shapes have two parallel sides